2018
DOI: 10.1016/s2095-3119(17)61901-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term green manure application on the content and structure of dissolved organic matter in red paddy soil

Abstract: Dissolved organic matter (DOM) plays important roles in soil biogeochemistry activity and nutrients transportation in soils, but studies regarding the long-term effects of green manures on the content and structure of DOM in red paddy soil have not been reported yet. A long-term green manure experiment established in 1982 was utilized to test the DOM contents in different treatments, and the spectral characteristics of DOM were investigated by using ultraviolet-visible (UV-Vis) spectrometry and Fourier transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(32 citation statements)
references
References 42 publications
2
27
0
3
Order By: Relevance
“…6b, c). As noted previously, low rates of ammonium supply and alkaline soil in our study site could be a benefit for the AOB keystone species (Nitrosospira , Table S4) (Ke et al 2013;Gao et al 2018).…”
Section: General Function and Specific Function With Community-level Diversitymentioning
confidence: 52%
“…6b, c). As noted previously, low rates of ammonium supply and alkaline soil in our study site could be a benefit for the AOB keystone species (Nitrosospira , Table S4) (Ke et al 2013;Gao et al 2018).…”
Section: General Function and Specific Function With Community-level Diversitymentioning
confidence: 52%
“…In southern China, with abundant water and heat resources but typically hilly areas, legume or grass mulches as cover crops in hilly orchard and legume-based rotations are recommended to reduce continuous cropping and improve soil quality. For example, applying green manure e.g., Chinese milk vetch in rice field of subtropical China can enhance the quantity and quality of soil organic matter [76,77] . Overall, the region-specific design of crop diversification will aim to concurrently achieve safe, nutritious food production and environmental protection.…”
Section: Synchronizing Safe and Nutritious Food Production With Environmental Protectionmentioning
confidence: 99%
“…When Mulumba and Lal studied the effects of straw mulch on soil physical properties in Ohio, USA, it was found that the soil moisture content increased with the increase of straw mulch, but after more than 8 Mg ha -1 , the soil moisture did not increase significantly, so they thought 8 Mg ha -1 was the suitable mulching application rate [39]; when studying the effects of different straw mulch application rate on water storage and water conservation of spring maize field in the dryland area of North Wei River in China, it was considered that 9 Mg ha -1 was the appropriate straw mulch application rate for spring maize in the dryland of North Wei River and the similar ecological area in combination with the grain yield and water conservation benefits of straw mulch [40]; however, in this study, based on the short-term organic mulch experiment, it was found that the soil moisture content did not increase significantly when the straw mulch application rate exceeds 5.556 Mg ha -1 . Organic mulch and its decomposition products can improve soil structure and soil water infiltration rate by enhancing soil aggregate stability and increasing soil porosity [41][42][43], but it should be noted that the continuous increase of straw mulch may impart water repellent and hydrophobic properties to the soil surface and restrict water infiltration [44]. This further indicates that although straw mulch plays an important role in soil moisture conservation, there is not a simple positive proportional linear relationship between straw mulch application rate and soil moisture content.…”
Section: Straw Mulch Application Ratementioning
confidence: 99%